A retrospective study of different treatments of limited‐stage small‐cell esophageal carcinoma and associated prognostic factor analysis. Issue 7 (14th January 2013) - Ding, J.; Ji, J.; Zhu, W.; Zhou, K.; Han, J.; Zhang, Y.; Yu, C.; Li, T.; Tao, G.; Ji, F.; Zhou, X.; Pan, P.
Summary Primary, small‐cell esophageal carcinoma (SCEC) is a rare but highly malignant tumor. Due to lack of randomized, controlled, prospective studies, there are currently no unified treatment modalities for SCEC. This study retrospectively analyzed the outcomes of different treatments and prognostic factors that influence overall survival in patients with limited‐stage SCEC. The study included 106 patients pathologically diagnosed with limited‐stage SCEC at Huai'an First People's Hospital, Nanjing Medical University (Huai'an, China), between 1998 and 2007. There were 66 males and 40 females, with a median age of 58 years (range: 45–77 years). Fourteen patients received surgery alone, 42 received surgery and postoperative chemotherapy, 11 received radiotherapy alone, and 39 received concurrent chemoradiotherapy. Combined modality treatment with and without chemotherapy yielded 5‐year survival rates (5YSRs) of 27.2% and 0%, respectively. Associated median survival times were 22 months and 11 months, respectively, with a hazard ratio (HR) of 2.30 (95% confidence interval [CI]: 1.42–3.73, P = 0.001). Among patients treated with surgery plus postoperative chemotherapy or with concurrent chemoradiotherapy, the 5YSRs were 31.0% and 23.1%, respectively. Median survival times were 26 months and 18 months, with an HR of 1.25 (95% CI: 0.75–2.09, P = 0.725). Multivariate survival analysis using Cox regression model showed that chemotherapy was a positive independent prognostic factor for SCEC (HR 2.92, 95% CI: 1.25–6.80). Chemotherapy‐based combined modality treatment appears to increase the long‐term survival of patients with limited‐stage SCEC. Similar overall survival rates results are achieved with surgery combined with chemotherapy as with concurrent chemoradiotherapy, with chemotherapy being an independent prognostic factor. Randomized, controlled, prospective studies are needed to identify optimal chemotherapy regimens for treating SCEC.